PO 134 - Coagulopatia iatrogénica: o papel do anestesiologista no perioperatório - Costa Barbosa, João; Valentim, Maria; Almeida, Mariana; Costa, Dinis; Louro, Juliana; Soares, Elsa (Journal of the Portuguese Society of Anesthesiology, 2023)
x